2017
DOI: 10.1016/j.yjmcc.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Aicar treatment reduces interstitial fibrosis in aging mice

Abstract: In 2030, elderly people will represent 20% of the United States population. Even now, chronic cardiac diseases, especially heart failure with preserved systolic function (HFpEF), are the most expensive DRGs for Medicare. Progressive interstitial fibrosis in the aging heart is well recognized as an important component of HFpEF. Our recent studies suggested an important pathophysiologic role for reduced TGF-β receptor 1 (TGFβR1) signaling in mesenchymal stem cells (MSCs) and their mesenchymal fibroblast progeny … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 15 publications
(28 reference statements)
0
17
0
Order By: Relevance
“…This is thought to occur in response to inflammation that facilitates natural repair of the endometrium (Gnainsky et al 2015). Through conditional mutagenesis studies or pharmacological activation, AMPK has been shown to reduce fibrosis and/or failure of scars to mature following injury in the liver (Ramezani-Moghadam et al 2015, Liang et al 2017, heart (Hermida et al 2013, Noppe et al 2014, lung (King et al 2012, Sato et al 2016, Tao et al 2017, kidney (Kim et al 2015, Thakur et al 2015, intestine (Cieslik et al 2017), peritoneum (Shin et al 2017, Zheng et al 2017, and adipose (Luo et al 2016). Our findings place AMPK at the center of the unique regenerative process within the endometrium that is essential for maintenance of fertility in the female.…”
Section: Discussionmentioning
confidence: 99%
“…This is thought to occur in response to inflammation that facilitates natural repair of the endometrium (Gnainsky et al 2015). Through conditional mutagenesis studies or pharmacological activation, AMPK has been shown to reduce fibrosis and/or failure of scars to mature following injury in the liver (Ramezani-Moghadam et al 2015, Liang et al 2017, heart (Hermida et al 2013, Noppe et al 2014, lung (King et al 2012, Sato et al 2016, Tao et al 2017, kidney (Kim et al 2015, Thakur et al 2015, intestine (Cieslik et al 2017), peritoneum (Shin et al 2017, Zheng et al 2017, and adipose (Luo et al 2016). Our findings place AMPK at the center of the unique regenerative process within the endometrium that is essential for maintenance of fertility in the female.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the number of mesenchymal fibroblasts is also reduced. Mechanically, AICAR-mediated AMPK activation inhibits the deposition of ECM and fibrosis in aging heart [57]. Aging promotes cardiac inflammation, the effect was attenuated by migration inhibitory factor (MIF) knockout.…”
Section: Inflammationmentioning
confidence: 99%
“…AICAR (5-aminoimidazole-4-carboxyamide ribonucleoside) is an agonist of the AMPK pathway. Previous studies showed that AICAR treatment reduced tubulointerstitial and interstitial fibrosis [11, 12]. In this study, we aimed to determine whether AICAR could ameliorate portal hypertension in an animal model.…”
Section: Introductionmentioning
confidence: 99%